IMPLEMENTASI PENGGUNAAN E-LEARNING DALAM PENGUASAAN KETERAMPILAN PEMERIKSAAN PAYUDARA PADA MAHASISWA KEBIDANAN: Implementation Of The Use Of E-Learning In Mastering Breast Examination Skills In Midwifery Students - Luluk Yuliati (LPPM - STIKES Pemkab Jombang, 2022)
E-learning for all levels of education is currently continuing to be extended with an increase in cases of covid-19 which has not shown a decline. Vocational education, especially health, experiences many obstacles in drastic learning changes. This study aims to identify whether there are differences in the value of clinical breast examination skills of midwifery students using e-learning and face-to-face methods. This research is a type of Quasi experiment. The research population was all 41 midwifery students, with a total sample of 20 people and the sampling technique was purposive sampling. The bivariate analysis used in this study is the independent samples t-test. The results of the analysis show the value of t (0.671 P> 0.05) so that it can be concluded that there is no difference in the use of e-learning media face-to-face on breast examination skills in midwifery students. This research proves that e-learning can be used as an alternative learning in mastering the skills of midwifery students, which is as effective as the face-to-face method.